The Influence of Teacher Characteristics on Learning Motivation in Students’ Economics Learning at Class XI IPS1 MAN 2 - Satriani, Satriani (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to determine the influence of teacher characteristics on student learning motivation. The type of research used is quantitative research methods. The data processed is the result of data collection through the distribution of questionnaires given to each classThe research results obtained by the author, namely hypothesis testing, show that the value of tcount > ttable is 3.109 > 2.064. Therefore, the value that has been obtained can be said to mean that H0 is rejected and H1 is accepted with a significance value of 0.005 < 0.05. It is said that there is an influence of teacher characteristics on learning motivation in economics learning for class XI IPS 1 MAN 2 Bone.